PENELITIAN KEKUATAN STRUKTUR SIRIP ASIMETRI ROKET SPIN TERHADAP PERBEDAAN GEOMETRI - Lidia Kristina Panjaitan (Pusbindiklat - LIPI, 2009)
Spin rocket represents one of the rockets that are designed to be able to reach bigger trajectory and accuracy of target. However it was required to be reckoned the influence of unsymmetric fin platform structure, which its most optimal performance by the effect of loading aerodynamic. By examination of structure strength through loading of bending moment with simulation of NXNASTRAN / FEMAP four unsymmetric fin design, so that maximum tension, minimum tension, tension around loading area and influence form fin plafform could be obtained.